Characterization and fungicides sensitivity of Colletotrichum species causing Hydrangea macrophylla anthracnose in Beijing, China - Zhao, Juan; Cheng, Yanli; Liu, Yayong; Shi, Xiaojing; Zhang, Taotao; Qin, Wentao (Frontiers in Plant Science, 2025)
Hydrangea macrophylla (Thunb.) Ser. is one of the widely cultivated plants in home gardens and scenic areas of China. Anthracnose disease is commonly observed during the normal growth of H. macrophylla, significantly impacting its ornamental and economic values. From 2021 to 2023, an investigation on H. macrophylla anthracnose was carried out in nine parks of Beijing, China, and a total of 114 Colletotrichum isolates were obtained from the diseased leaves with typical anthracnose symptoms. Based on morphological characteristics and phylogenetic analysis of six genomic loci including rDNA-ITS, ACT, TUB2, CAL, CHS-1, and GAPDH, these isolates were identified as belonging to six Colletotrichum species. Among which, C. gloeosporioides was the most abundant (65 isolates, 57.0%), followed by C. fructicola (33 isolates, 28.9%), C. aenigma (8 isolates, 7.0%), C. truncatum (4 isolates, 3.5%), C. subacidae (2 isolates, 1.8%) and C. sojae (2 isolates, 1.8%). Pathogenicity test conducted on detached leaves of H. macrophylla revealed a distinct variation in virulence among isolates from different Colletotrichum species, and wounding was either essential or conducive to successful infection. Specifically, C. gloeosporioides exhibited greater aggressiveness, resulting in larger lesions, while C. subacidae induced lesions most quickly. Fungicide sensitivity assays demonstrated that prochloraz exerted a remarkable inhibitory effect on the mycelial growth of representative isolates belonging to the three predominant Colletotrichum species. In contrast to difenoconazole and tebuconazole, the mean EC50 values for prochloraz against C. gloeosporioides, C. fructicola, and C. aenigma were 0.062, 0.033, and 0.023 μg/ml, respectively. This is the first report of C. aenigma, C. truncatum, C. subacidae and C. sojae causing H. macrophylla anthracnose worldwide including China. These findings have elucidated the Colletotrichum species associated with H. macrophylla anthracnose as well as their fungicides sensitivities in Beijing, China. This provides a scientific foundation for the accurate diagnosis and local management of H. macrophylla anthracnose.